PENGARUH PERLAKUAN PERENDAMAN AIR PANAS DANAIR DINGIN TERHADAP PERKECAMBAHAN BENIH KARET (Hevea brasilliensisMuell.Arg) DAN SUMBANGSIHNYA PADA MATA PELAJARAN BIOLOGI MATERI PERTUMBUHAN TUMBUHANKELAS XII SMA / MA - Zainal Berlian; Syarifah Syarifah; al Hidayat (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2016)
Rubber tree (Hevea brasiliensis, Muell.Arg) belongs to the family Euphorbiaceae, called by other names rambung, sap, members, kejai or hapea. Rubber seed is the result of another addition to natural rubber from the rubber tree (Hevea brasiliensis, Muell.Arg) were underused. Rubber seeds are large and have a leather or hard shell. Most people still use rubber seed as a seed to be planted. This study aims to determine the effect of soaking treatment of hot water and cold water on the seed germination of rubber (Hevea brasilliensis, Muell. Arg). This research was conducted at the Laboratory of Biology UIN Raden Fatah Palembang in South Sumatra. The parameters observed in this study was the rate of germination and seed vigor index. This study uses a completely randomized design (CDR) with 4 treatments, without treatment (control), immersion in hot water, cold water immersion and immersion hot water then in cold water, the number of seeds 20 on each - each treatment. The results of the study are in the treatment of hot water immersion C2 and submerged into cold water are the parameters of the best with 85% germination percentage and seed vigor index of 9.64. This reseach contributed to the world of education is in the form of student worksheets and lesson plan.